2020
DOI: 10.1101/2020.03.10.986224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SUMOylation of rice DELLA SLR1 modulates transcriptional responses and improves yield under salt stress

Abstract: Author Contributions: 15 NMG participated in the conception of research, executed most experiments, and 16 wrote the article with contributions from all authors. TF did protein interaction 17 experiments. MTGR characterized SUMO-protease rice lines. CCM analysed data 18 and completed the writing. MAAR purified recombinant proteins. PMB analysed RNA 19 seq. MMO supervised experiments and analysed results. IAA conceived original 20 project, supervised experiments, and finalised the article. 31 32 Short title (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Different herbicides and stresses, such as salinity, affect morphological, biochemical, physiological, and molecular attributes in crops and weeds [10,[46][47][48][49][50]. Different responses at different biological levels have been studied in cultivated rice under salt stress [51][52][53]. However, there is little information about weed behavior under these conditions, and the weed response to a combination of herbicide and salinity stresses, which could be imprinted into the genome of succeeding generations.…”
Section: Discussionmentioning
confidence: 99%
“…Different herbicides and stresses, such as salinity, affect morphological, biochemical, physiological, and molecular attributes in crops and weeds [10,[46][47][48][49][50]. Different responses at different biological levels have been studied in cultivated rice under salt stress [51][52][53]. However, there is little information about weed behavior under these conditions, and the weed response to a combination of herbicide and salinity stresses, which could be imprinted into the genome of succeeding generations.…”
Section: Discussionmentioning
confidence: 99%
“…However, DELLA stabilisation causes high DELLA levels and reduced fertility [264]. Rice DELLA SLR1 also undergoes SUMOylation, which alters its interaction with specific transcription factors to improve abiotic stress tolerance [265]. There is a suggestion that SLR1 SUMOylation may attenuate the penalty of salt stress tolerance on plant yield [265], with the goal of maintaining yield and disease resistance under pathogen stress in rice, which would be interesting to explore.…”
Section: Growth-defence Trade-offsmentioning
confidence: 99%
“…Rice DELLA SLR1 also undergoes SUMOylation, which alters its interaction with specific transcription factors to improve abiotic stress tolerance [265]. There is a suggestion that SLR1 SUMOylation may attenuate the penalty of salt stress tolerance on plant yield [265], with the goal of maintaining yield and disease resistance under pathogen stress in rice, which would be interesting to explore. In addition, mutation of the SIM site in GID1 in rice or Arabidopsis could be manipulated to fine-tune DELLA degradation [263].…”
Section: Growth-defence Trade-offsmentioning
confidence: 99%
“…A recent study revealed that the rice SLR1 was SUMOylated at K2 but not at K60 (the position equivalent to K65 in RGA), suggesting that DELLA SUMOylation operates differently in monocots and eudicots. In turn, SLR1 can be deSUMOyated by the FUG1 SUMO protease ( Gonçalves et al. 2020 ).…”
Section: Sumoylation: Control Of Both Della Stability and Activitymentioning
confidence: 99%
“…2A ). Rice plants overexpressing SUMO–SLR1 displayed improved tolerance to salt stress and altered expression of genes involved in the defense response and in GA metabolism ( Gonçalves et al. 2020 ).…”
Section: Sumoylation: Control Of Both Della Stability and Activitymentioning
confidence: 99%